Using Robot Kits for Teaching Railway Engineers - Lai, Y.; Chi, Hung-Lin; Cheng, W.; Kang, S. (International Council for Research and Innovation in Building and Construction, 2012)
This paper describes a methodology that uses robot kits for teaching railway engineering. Current railway engineering courses focus more on the theories of railway design and management. The lack of hands-on experience of students may result in design defects in practice. Automation and Robotics, an optional course designed for senior students in the Department of Civil Engineering at National Taiwan University, was specifically designed as a 4-week courseware for training future railway engineers. In addition to studying the theory of railway control systems, students were required to implement a railway control system using the robot toolkit LEGO Mindstorm NXT, and the robot platform Microsoft robotics developer studio (MSRDS). After the4-week course, as a final project students were divided into six teams and demonstrated their automatic train control (ATC) systems. From the project demonstration, we found that the designs of all six teams were conceptually very similar, differing only in certain characteristics. Four of the six teams successfully delivered stable ATC systems. According to feedback obtained from the questionnaires, students had a very positive learning experience. Therefore, the authors conclude that the incorporation of these hands-on training techniques into advanced design courses will be very successful.